Does Gender Moderating The Influence Of Iq, Eq, Sq, On Financial Management Behaviour Of The Sandwich Generation In Demak District ? - Dayana, Putri; Ira Setiawati; M. Fadjar Darmaputra (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
ABSTRACT This study aims to test and analyze the influence of IQ, EQ, and SQ on Financial Management Behavior with Gender as a Moderating Variable in the Sandwich Generation in Demak Regency. This study uses the Structural Equation Model Partial Least Square (SEM-PLS) method with Smart-PLS 3 to test and analyze the data. The population used in this study were 96 respondents who were working students/sandwich generation domiciled in Demak Regency. The sampling technique in this study used purposive sampling by meeting the criteria including working students/sandwich generation Someone who bears the costs above (parents) and below (children or their siblings) in Demak Regency with an error rate of 10%. Based on the results of the study, it was found that IQ had a positive and significant effect on financial management behavior, EQ had a positive and significant effect on financial management behavior, SQ had a negative and insignificant effect on financial management behavior, gender could not significantly strengthen the effect of IQ on financial management behavior, gender strengthened the effect of EQ on financial management behavior insignificantly, and gender could insignificantly strengthen the effect of SQ on financial management behavior. Keywords: IQ (Intelligence Quotient), EQ (Emotional Quotient), SQ (Spiritual Quotient), Financial Management Behavior, and Gender.